“I surely don’t call for fun”: experiences of being a “frequent caller” to the Danish emergency helpline - Camilla Braendstrup Laursen; Tine Bennedsen Gehrt; Linda Huibers; Claus Bossen; Ulla Vaeggemose (BMC Public Health)
Abstract Background While most Danish citizens never or very rarely call the national emergency helpline, 1-1-2, a few citizens call very often. In this article, we attend to the often-unheard voices of frequent callers, exploring why these citizens call 1-1-2 and why they often do not feel helped. Methods The article is based on a mixed-methods study on citizens in the Central Denmark Region who had called 1-1-2 five or more times during a period of six months in 2023. The study drew on call data, questionnaires, and telephone interviews. In this article, we focus on the 12 citizens who participated in a semi-structured telephone interview. The interviews were transcribed verbatim and coded twice. Through abductive analysis of the data, we found Desjarlais’ concept of “struggling along” to be a useful theoretical lens. Results We found that our study participants “struggled along” in life and that they called 1-1-2 when they could not cope with their health conditions and difficult life circumstances themselves, and when neither their social networks nor the welfare society could help them out. Furthermore, we found that the sense of disorientation and the fragmentation of experience that is characteristic of “struggling along” made it difficult for our study participants to communicate with the Emergency Medical Coordination Center (EMCC) that manages all health-related calls to 1-1-2. Finally, our analysis pointed to differences in how the goal of providing “the right help at the right time” was understood by citizens and by health professionals working within the EMCC of the Prehospital Emergency Medical Services. Conclusions Overall, our study adds to the very limited literature on the experiences of frequent callers to emergency medical helplines. It emphasizes that frequent callers are people who call for help because they continue to need help, and it points towards the necessity of developing alternative interventions to help this diverse group of people.